Avances en la propuesta curricular núcleo clínico (1998)
ABSTRACT: The process of curricular building in the clinical nucleus starts from a global view of the socio-economic, politic, and legal legislative context in health, education, and nursing to a domestic and international level. The process of curricular construction propose to strengthen research, establishing line son the object on the nursing knowledge to educate with an understanding of the professional role in order to work together with the other disciplines to response to health problems. Furthermore, this group of teachers analyse the term clinic, nucleus, and scope and it meaning for the profession. This group considers that the teaching nucleus School of Nursing is the Nursing care, answering what, how, when, where, and what for of such care. Finally, as fundamental element, it is proposed to collect and systematize teachers and graduates experiences in order to select, by the light of these experiences and from a global vision of curriculum, the basic experiences and subjects for education and to organise the curriculum the subjects directing it to the achievement of goals and the profile of education.